A rare case of long-standing intracranial hypertension secondary to a lumbosacral extradural tumor - Neto, Eduardo Bernardo Chaves; Naback , Juliana; Silva, Natália de Oliveira; Teng, Erik Zhu; Sousa, Eduardo Luiz Alves de; Cetlin, Roberto Satler; Dach, Fabíola (Headache Medicine, 2024)
Introduction: Intracranial hypertension (ICH) caused by a spinal cord tumor is a rare but well-known condition. Identifying the disease is particularly challenging when characteristic spinal symptoms or signs are absent. Objective: To report a rare case of long-standing intracranial hypertension secondary to a lumbosacral extradural tumor. Case Report: A 76-year-old male patient, a former smoker and alcohol consumer, with a 10-year history of headache associated with visual impairment and bilateral papilledema, which was diagnosed as idiopathic intracranial hypertension. One year ago, he developed mental confusion, imbalance, and gait disturbances. Sixty days before admission, he presented weakness in the lower limbs, and 15 days before admission, he experienced new-onset seizures. On examination, anisocoria (right larger than the left), sluggish pupillary reaction to light in the left eye, and visual acuity of counting fingers at 4 meters in the right eye and 20/80 in the left eye. Fundoscopy showed optic nerve pallor (grade 2+), papillary edema with 360-degree blurring (Frisen grade 4). Complementary laboratory tests included cerebrospinal fluid (CSF) analysis, collected via suboccipital puncture, with an opening pressure of 35 cmH2O and a protein level of 81 mg/dL. Magnetic resonance imaging (MRI) and angiography of the brain showed a partially empty sella and diffuse proportional cerebral atrophy. The patient underwent optic nerve fenestration and subsequently a ventriculoperitoneal shunt to relieve intracranial pressure and reduce optic nerve suffering. Further investigation for causes of elevated CSF pressure and recent neurological findings, including motor loss, led to a spinal MRI revealing an intradural lesion between L4-S1, approximately 6.1 cm in craniocaudal axis, with posterior bone remodeling between L5-S1 inferring compression of the cauda equina roots, without involvement of the conus medullaris. Spinal arteriography confirmed a hypervascular lesion at levels L4 to S1, with blood supply from the anterior spinal artery and ectasia of the medullary drainage veins. After neurosurgical evaluation, the patient, in clinical stability, chose not to further stratify the lesion. Conclusion: Since intracranial hypertension can lead to a permanent optical loss, spinal MRI may be considered soon after the initial investigation to exclude atypical and rare cases of intracranial hypertension.